Creative teaching in virtual environments for the development of emotional competencies - Aragundi, Ketty (2021)
The present research conducted at the upper basic level of the "José María Santana Salazar" Educational Unit of the Manta canton, had the objective of analyzing the influence of creative teaching in virtual environments, to develop emotional competencies in students.  A qualitative, exploratory approach was used to collect the points of view of teachers and experts on the subject through the interview instrument, applied to a purposive sample.  The results showed that teachers include creative strategies through motivational messages, positive attitudes, empathy, curious data, visual dynamics, among others, to create favorable environments for teaching and learning. It is concluded that virtual environments have not allowed the satisfactory development of emotional competencies in students, presenting inconveniences in the adaptation of the current study modality. For this reason, teachers have had to be trained in an accelerated way to cope with the demands of virtual education, applying creative and innovative strategies.